Missio Dei and the challenge of prosperity practices: A missiological critique from the Global South, focusing on East Africa - Richard Ondicho Otiso (Phronesis: Jurnal Teologi dan Misi, 2026)
This article offers a sharply critical missiological examination of the growing dominance of prosperity-oriented practices within churches in the Global South, with particular focus on East Africa. It argues that the prosperity gospel has effectively displaced the Missio Dei—God’s mission of reaching sinners with the saving message of Jesus Christ—by substituting the gospel of salvation with a transactional religion of wealth acquisition. Drawing on the works of David Bosch, Lesslie Newbigin, Kate Bowler, and Paul Gifford, the article demonstrates that prosperity teaching has become more attractive to many churchgoers than the gospel of repentance and redemption, a trend that should alarm every serious theologian and pastor. In East Africa, vulnerable believers have been manipulated into selling their properties, emptying their savings, and surrendering their livelihoods to churches and pastors who promise miraculous financial returns—effectively reducing God to an Automated Teller Machine or a cosmic lottery. This article contends that such practices constitute a fundamental betrayal of the church’s missional vocation, a form of spiritual abuse, and an affront to the character of God. It proposes a prophetic recovery of Missio Dei grounded in the proclamation of salvation, justice for the poor, and the dismantling of exploitative ecclesial structures.